2007
DOI: 10.1002/adfm.200700251
|View full text |Cite
|
Sign up to set email alerts
|

Control of Specular and Diffuse Reflection of Light Using Particle Self‐Assembly at the Polymer and Metal Interface

Abstract: We present a novel method of controlling the specular and diffuse reflection of light by the electrostatic deposition of a spherical particle monolayer followed by electroless plating. Charged polystyrene colloidal particles, ranging in size from 100 nm to 5 μm, were adsorbed from solution onto oppositely charged polyelectrolyte multilayers (PEM). The monodisperse particle monolayers were coated with nickel in a two‐step electroless plating process using palladium catalysts. These surfaces can be used as diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Alternatively, smooth surfaces could produce either specular or diffuse reflection, depending on the surface type. Research on this idea has been carried out 32 in other fields of study, but is not sufficient at present, to be able to define the particular reflecting behaviour of these metal surfaces. This would be an interesting study to pursue to better understand reflection of UV from metal surfaces in urban environments.…”
Section: Why Does the Uv Reflection Change?mentioning
confidence: 99%
“…Alternatively, smooth surfaces could produce either specular or diffuse reflection, depending on the surface type. Research on this idea has been carried out 32 in other fields of study, but is not sufficient at present, to be able to define the particular reflecting behaviour of these metal surfaces. This would be an interesting study to pursue to better understand reflection of UV from metal surfaces in urban environments.…”
Section: Why Does the Uv Reflection Change?mentioning
confidence: 99%
“…Although some electrostrictive and mechanical properties enhanced, 25 the optical transmittance is expected to be deteriorated as increasing crystallinity of polymer films. The reduction in transmission intensity is mainly the result of light scattering at the surface or the bulk of semicrystalline film.…”
Section: Effect Of Crystallinity On Surface Morphology and Optical Trmentioning
confidence: 99%
“…This phenomenon was most likely caused by the arrangement of the particles on the outermost surface layer. 31,32 In contrast, the rough surfaces on the interior of the plates were obtained (Fig. 4b.…”
mentioning
confidence: 92%
“…4b. 31,32 The aforementioned results indicate that the textures of the structural color materials were controlled by the balance between the specular and diffuse reectance from the arrangement of PDA black particles. 30 Previous studies have shown that at surfaces made of colloidal materials increase the specular reectance and produce a metallic texture.…”
mentioning
confidence: 99%